Khentii-Dornod Khamnigan Ewenki: Toward a revised analysis of Rinchen’s notes on a Tungusic language of Mongolia - SHIMUNEK, Andrew (2019)
This paper discusses my efforts in analyzing the important linguistic data on Khentii-Dornod Khamnigan Ewenki, a probably now extinct Tungusic language of Mongolia documented by the Mongolian scholar Academician B. Rinchen in the 1960s and published in his book, Mongol Ard Ulsîn Xamnigan Ayalguu [The Tungusic Dialects of the Mongolian People’s Republic]. Rinchen’s book is essentially the only source of linguistic data on Khamnigan Ewenki as once spoken in the provinces of Khentii and Dornod in northeastern Mongolia; however, the data in Rinchen’s book is largely unanalyzed and much progress has been made in the field of language description since the publication of Rinchen’s book. In this paper, I present some findings of my work toward a revised analysis of Rinchen’s notes, including an interpretation of the phonological inventory, morphological analyses, notes on the lexicon, and my efforts toward a sketch grammar of Khentii-Dornod Khamnigan Ewenki based on Rinchen’s data. My reanalyses of Rinchen’s data currently consist of an interpretation of the phonological values intended by Rinchen’s practical Cyrillic transcriptions of Khamnigan Ewenki data, reanalyses of morphemes and lexical items transcribed by Rinchen but not fully analyzed, a revised analysis of several short Khamnigan Ewenki texts documented by Rinchen, sentential data, and notes on the lexicon.